FAKTOR-FAKTOR YANG MEMPENGARUHI HARGA CABAI MERAH BESAR DITINGKAT PEDAGANG PENGECER KABUPATEN OGAN KOMERING ULU (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2020)
This research analyzed the factor that influence the price of chilie in the level of retailer in Ogan Komering Ulu regency, accumulation the data was did on March until April 2017. The research method that used in this research was survey method by using the questionnaire as a tool of the research that took the sample from the population, the data that was used primer and sekunder. In analyzing the data research use regression linear berganda. Based on the of the research, the factors that influence the price of chilie on the retailer level in Ogan Komering Ulu regency was 0.170 production variable influenced on degree α = 0.15 %, The demand variable was – 0.217 influenced on the degree α = 0.15 % and the climate variable was – 4948.537. it was very influenced on degree α = 0.01 %.